Exploring advance care planning discourses in scottish dementia policies: A critical discourse analysis - Tharin Phenwan; Judith Sixsmith; Linda McSwiggan; Deans Buchanan (Social Sciences and Humanities Open)
Advance Care Planning (ACP) is a continuous process that enables individuals to discuss and document their preferences for future care in the event of terminal illness or incapacitation. In Scotland, the creation of ACPs is encouraged and integrated into current dementia policies as a means of safeguarding the human rights of people living with dementia (PwD). However, the uptake of ACP amongst PwD remains low, potentially due to PwD's fluctuating mental capacity and symptoms of forgetfulness. Moreover, the ACP process, which is typically aimed at healthcare professionals (HCPs), may not be suitable for PwD due to the lack of appropriate support they might need to fully engage with the ACP process which includes meaningful conversations, documentation and regular review.This study employed Fairclough's Critical Discourse Analysis to explore how the discourses in Scottish dementia policies influence the initiation and revision of ACP for PwD. It examined how the voices of PwD, family carers, and HCPs shaped dementia policies regarding the initiation and revision of ACP.Three discourses were identified: Shifting Agencies, Formulaic Rightness, and Visibility and Voices. The analysis revealed that dementia policies inadequately supported the initiation and revision of ACPs for PwD. This is attributed to the responsibility for initiating ACPs being variously ascribed to different stakeholders, creating ambiguity regarding process ownership. The ACP process is presented in policy as formulaic, ignoring the nuances of PwD's circumstances. The input and participation of PwD, family carers, and HCPs in policy related to ACPs was less visible, thus calling into question the legitimacy of those policies.In light of these findings, the person(s) responsible for supporting the ACPprocess with and for PwD should be made explicit. The notion of ACP revision, which aims to reflect PwD's changing needs, warrants greater emphasis within these dementia policies.